USING GRAPHIC MODELING TO DETERMINE THE ANGLE BETWEEN THE ROLL AXES OFVEHICLES AT THE MOMENT OF COLLISION - S. Zharkikh (Теория и практика судебной экспертизы, 2015)
An algorithm is proposed for determining the angle of relative position of vehicles at the moment of collision, using a graphic modeling method that involves building a damage model.